Social Safety Network (JPS) Policy To Communities Affected By Covid-19 Pandemic In Batang District, Central Java - Muhammad Nashruddin (Veteran Justice Journal, 2021)
Abstract Since the announcement that COVID-19 is a government, it has made several efforts to reduce the massive expansion of COVID-19. The implementation of Large-Scale Social Restrictions (PSBB), as well as adaptation to new habits or new normal has been instructed by the government for the community. However, these efforts have still not been able to show success in efforts to suppress the development of the spread of the corona virus in Indonesia. The COVID-19 pandemic in Indonesia has led to a socio-economic crisis whose impact can be felt by all levels of society, especially the 40% of people with low levels of welfare. national disaster, the spread of this virus in Indonesia has not shown a decline. Therefore, in crisis management, the government implements the Social Safety Network (JPS) program to encourage economic growth in times of crisis. Long before the COVID-19 outbreak, the Social Safety Net (JPS) program was an important component of the economic crisis that hit Indonesia in 1998. The JPS program was part of a government microeconomic policy in facing the economic crisis. Keywords: JPS, Government Programs, Covid-19